The Analysis of Students’ Inferiority Feeling on Speaking Ability - Akhmad, Syahrul Ma’arif; Sugiharto, Prasetyawan Aji; Santoso, Yan Imam (Universitas Muhammadiyah Mataram, 2025)
Speaking is an English language skill that should be mastered by EFL learners. This study aims to know the factors that induce students’ inferiority in speaking English in the second semester of English education at the Muhammadiyah University of Kendal Batang. This research is the Descriptive-qualitative method and uses applied purposive sampling techniques in choosing sampling. 26 students as respondents experienced inferiority feelings in class, second-semester students of English education at the Muhammadiyah University of Kendal Batang. The data was obtained through an observation checklist, distributed open-ended questionnaire, and an interview. There were 5 factors the results in this research showed caused students’ inferiority feeling in speaking English. The majority of factors are lack of vocabulary 26%, followed by unconfident about 24%, fear of making mistakes 21%, fear of negative reaction 18% and grammar problems 11%. So, it can be concluded that the problems of students’ speaking are not only from the internal, but it’s also from external. Teacher should influence the students to speak up without anxiety. Using some appropriate methods and supportive environment may can help students in speaking well.